UJI AKTIVITAS ANTI-INFLAMASI KRIM EKSTRAK ETANOL BAWANG DAYAK (Eleutherine palmifolia (L) Merr) PADA LUKA SAYATAN TIKUS PUTIH JANTAN - Amalia Khairiah; Eka Wisnu Kusuma (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2021)
Inflammation is a body mechanism for destroy and disable organism that attack accompanied by inflammation with perfect healing process, inflammation can be treated with anti-inflammatory drugs non steroid and steroid. But that’s have an effects. Bawang dayak (Eleutherine palmifolia (L) Merr) contain flavonoid used to anti inflammatory. The objective to knowing anti-inflammatory effect of extract bawang dayak to incision wounds in male white rats. There is 5 method to used, that positive control with krim hidrokortison 2,5%, negative control with basis cream. Group 1 with give KEEBD 5%, group 2 with give KEEBD 10% and group 3 with KEEBD 15%. The test result used the Shapiro-wilk with one way anova (α=0,05) giving cream extract ethanol Bawang dayak (KEEBD) has an anti-inflammatory effect and closes the length of the cut with the most effective concrentration of 15%